Drug Repurposing: Exploring Potential Anti-Cancer Strategies by Targeting Cancer Signalling Pathways - Natalia Haddad; Sara Magura Gamaethige; Nadine Wehida; Ahmed Elbediwy (Biology, 2024)
The repurposing of previously clinically approved drugs as an alternative therapeutic approach to treating disease has gained significant attention in recent years. A multitude of studies have demonstrated various and successful therapeutic interventions with these drugs in a wide range of neoplastic diseases, including multiple myeloma, leukaemia, glioblastoma, and colon cancer. Drug repurposing has been widely encouraged due to the known efficacy, safety, and convenience of already established drugs, allowing the bypass of the long and difficult road of lead optimization and drug development. Repurposing drugs in cancer therapy is an exciting prospect due to the ability of these drugs to successfully target cancer-associated genes, often dysregulated in oncogenic signalling pathways, amongst which are the classical cancer signalling pathways; WNT (wingless-related integration type) and Hippo signalling. These pathways play a fundamental role in controlling organ size, tissue homeostasis, cell proliferation, and apoptosis, all hallmarks of cancer initiation and progression. Prolonged dysregulation of these pathways has been found to promote uncontrolled cellular growth and malignant transformation, contributing to carcinogenesis and ultimately leading to malignancy. However, the translation of cancer signalling pathways and potential targeted therapies in cancer treatment faces ongoing challenges due to the pleiotropic nature of cancer cells, contributing to resistance and an increased rate of incomplete remission in patients. This review provides analyses of a range of potential anti-cancer compounds in drug repurposing. It unravels the current understanding of the molecular rationale for repurposing these drugs and their potential for targeting key oncogenic signalling pathways.